Power system protection (Power and energy series, 1995)
The worldwide growth in demand for electricity has forced the pace of developments in electrical power system design to meet consumer needs for reliable, secure and cheap supplies. Power system protection, as a technology essential to high quality supply, is widely recognised as a specialism of growing and often critical importance, in which the power system needs and technological progress and combined to result in rapid developments in policy and practice in recent years. The Electricity Training Association has now commissioned a fourth volume covering digital technology. With the new fourth volume, the edition gives a comprehensive and up-to-date treatment of the subject, covering theory, analytical and design principles, equipment design and application and protection management